INTERPRETATIVE POSSIBILITIES OF SENSE DERIVATION WITHIN TRANSLATION PROCESS (ON THE OCCASIONAL SHIFT) - S. Bredikhin (Гуманитарные и юридические исследования)
In the article the adequate translation possibilities of occasional synereses and their interpretative potential within new sense construction as certain «acting scheme» in the multidimensional discourse are considered.